Heterosis and Reciprocal Effect For Body Weight and Leather Properties in Hybrid Goats - Afolabi T. Yusuff; Abdul-Hameed A. Badmos; Timothy R. Fayeye (Syiah Kuala University, 2017)
Identification and evaluation of economically important traits in livestock is central to genetic improvement. The objective of this study was to evaluate heterosis and reciprocal effects for bodyweight and leather properties among progenies of pure and reciprocal crossing of West African Dwarf (WAD) and Red Sokoto (RS) goats. Bodyweights of 96 kids were recorded at birth, weaning and yearling. Skins collected from slaughtered goats at yearling were processed to leather using vegetable tanning approach. The leathers were subjected to physical analysis to determine Thickness, Percentage Elongation (PE), Surface Area, weight and grain properties comprising Load at Crack, Load at Tear, Distension at Crack and Distension at Tear. Heterotic effect for bodyweight was negative at birth (-8.99%) and weaning (-11.15%) but positive at yearling (6.64%). Specific heterosis for bodyweight at yearling was higher for progenies of WAD does serviced with RS bucks. General and specific heterosis were positive for all the leather traits except PE. Specific heterosis was higher when RS does were serviced with WAD bucks. Reciprocal effects for bodyweight reduces with increase in goats’ age (Birth Weaning Yearling: 9.88 6.28 5.62).Reciprocal effects for grain properties were generally higher than other leather traits. This study concluded that WAD and RS goats are dissimilar in leather traits and bodyweight at different ages, and that choice of sire or dam for successful crossbreeding programme is trait dependent